ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN UNIVERSITAS SLAMET RIYADI DI SURAKARTA - Sarwono - (Innofarm:Jurnal Inovasi Pertanian, 2011)
ABSTRACT Target of this research is (1) to analysis factor what having significant and influence to employees performance Slamet Riyadi University in Surakarta. (2) to know factor which having an effect the strongest to employee performance in Slamet Riyadi Surakarta. Reuslt of research show: leadership variable, communication variable, reward variable, and motivation variable have and effect significant to employee performance Slamet Riyadi University. Examination of hypothesis accuracy of model (F test) show F value calculated equal to = 37,190 with level of significant 0,000. Probability value 0,000 < 0,05 matter give meaning that examination of used by model that is leadership factor, communication, reward, and motivation proven by at a time have strongest contribution in influencing employee performance. This matter because of level of regression coefficient value equal to = 0,449. is which the biggest to be compared with three of other variable. Result of determination coefficient (R²) show: 0,768 matter give meaning leadership variable, communication variable, reward variable, and motivation variable give contribution effect to employe performance Slamet Riyadi University ?6,8% and 23,2ºfo another variable not include in this model. (3) Result from assumption classical test conclude used regression model in this research do not happened heteroscedasticity show: LM value 0,65 < 9,2 do not happened autocorrelation DW test value 2,033 show 1,5< 2,033<2,5, and do not happened multicolinerity  tolerance test value < 0,1 and V1 F test < 10, and then can be said BLUE. Keyword: Leadership, Communication, Reward, Motivation and Employee Performance.